SISTEM PENDATAAN KEUANGAN KARANG TARUNA BERBASIS WEBSITE MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT - Taufik Ismail Riyanto; Bambang Santoso (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
This website-based youth youth financial data collection system was created to make it easier for youth leaders and administrators to collect data on fees, activities and membership, and is also used to efficiently manage and store data in the Sudimara Timur sub-district, Ciledug sub-district, Tangerang. A website-based youth financial data collection system using the rapid application development method is designed using the PHP programming language and MySQL database which in the final stage can function to facilitate data processing, for the implementation phase it uses UML (Unified Modeling Language) which can analyze input data and data. output. The Rapid Application Development (RAD) method is a method that focuses on developing applications quickly, through repeated repetition and feedback. To ensure that the system is running properly, two stages of testing are carried out, namely white box and black box testing in the member data collection process, managing event data and dues and testing in the process of displaying activity reports and member dues.